2022
DOI: 10.1109/jphot.2021.3135659
|View full text |Cite
|
Sign up to set email alerts
|

Spatially, Spectrally Single-Mode and Mechanically Flexible 3D-Printed Terahertz Transmission Waveguides

Abstract: Emerged terahertz transmission waveguides or fibers will enable novel terahertz systems and applications. Highquality output beam profiles, mechanical flexibility and reliability are among the most crucial and challenging characteristics of terahertz transmission waveguides. Here, we design and fabricate the flexible and stretchable transmission waveguides by 3D printing to guide radiation from terahertz (THz) quantum cascade lasers (QCLs) lasing at the frequency of 2.58 THz. Composite silver nanoparticles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Recently, the design and fabrication methods of THz waveguide devices based on 3D printing technique have been developed [25][26][27]. In 2018, Li et al fabricated a low-loss THz hollow waveguide by 3D printing technology, whose transmission loss and beam divergence angle were 0.015 cm −1 and 6.8 • , respectively [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the design and fabrication methods of THz waveguide devices based on 3D printing technique have been developed [25][26][27]. In 2018, Li et al fabricated a low-loss THz hollow waveguide by 3D printing technology, whose transmission loss and beam divergence angle were 0.015 cm −1 and 6.8 • , respectively [25].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Li et al fabricated a low-loss THz hollow waveguide by 3D printing technology, whose transmission loss and beam divergence angle were 0.015 cm −1 and 6.8 • , respectively [25]. In 2022, Chen et al demonstrated a 3D-printed flexible THz transmission waveguides, which is realized by coating composite silver nanoparticles and polydimethylsiloxane on the inner surface of the 3D-printed polycarbonate/rubber substrate tube [26]. In 2023, Xu and Skorobogatiy highlighted practical applications of 3D printed waveguides in manipulating THz waves, including the refractive index sensors, dispersion compensators, and adddrop multiplexers [27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the guided mode of dielectric waveguide is generally dominated by HE 11 , which can lead to serious crosstalk issues in fiber bundle. 8 In addition to the dielectric fiber bundle, a wire medium has been widely applied in the super-resolution THz imaging due to the extreme optical anisotropy and strong spatial dispersion. 38,39 Evanescent waves in free space can be transformed into TEM wave transmission in the wire medium, enabling a given field distribution to be transmitted through such structure with a minimal loss of resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The THz waveguide or fiber is an effective method to guide and deliver THz waves, which shows significant values in applications such as endoscopy and subwavelength resolution imaging. , Among all of the waveguide structures, hollow-core waveguides have proved to be significantly functional in imaging applications. For example, Lu et al proposed a fiber-scanning THz imaging system based on a subwavelength plastic fiber .…”
Section: Introductionmentioning
confidence: 99%
“…Although various metamaterial-based THz devices can realize the modulation function of THz waves, there are still some shortcomings, such as difficult material preparation, easy oxidation and corrosion, difficult integration, and so on [20][21][22][23]. In contrast, high-efficiency transmission waveguides and waveguide-type functional devices have shown greater advantages than the free space transmission of THz waves [24][25][26][27]. However, researchers have paid more attention to reduce the loss and dispersion of waveguides.…”
Section: Introductionmentioning
confidence: 99%